Graphene oxide water-based anticorrosive paint and preparation method thereof
Through electrochemical peeling and amino modification, graphene oxide is treated and fully mixed with aqueous resin and curing agent, the problem of graphene oxide agglomeration in the coating is solved, and its uniform dispersion and high efficiency in aqueous coatings are achieved Anti-corrosion performance.
Patent Information
- Application Number
- CN202411695717.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-25
AI Technical Summary
Graphene oxide is prone to agglomeration in the coating matrix, resulting in the inability to disperse uniformly and fully exert its excellent barrier properties, thereby reducing the corrosion resistance of the coating.
The expanded graphite stack is oxidized to graphene oxide by electrochemical peeling method, and its hydrophilicity is enhanced by amino modification, so that it is evenly dispersed in the aqueous coating. Then, the graphene oxide dispersion was fully mixed with the aqueous resin emulsion and the curing agent to prepare an aqueous anticorrosion coating.
The uniform dispersion of graphene oxide in the coating system and effective combination with the matrix are achieved, and the anti-corrosion performance of water-based coatings is significantly improved.
Smart Images

Figure CN119490784A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of water-based anti-corrosion coatings and preparation thereof, and in particular to a water-based graphene oxide anti-corrosion coating and a preparation method thereof. Background Art
[0002] Metal corrosion is one of the major issues faced by almost every industry, which not only brings huge economic losses and environmental pollution, but also easily causes major safety accidents. Using organic / inorganic or composite coatings as physical barriers is an important anti-corrosion method, and the performance enhancement of anti-corrosion coatings also mainly depends on the physical and chemical properties of the fillers embedded in the matrix.
[0003] Among nano-scale carbon-based fillers, graphene oxide (GO) is widely used in anti-corrosion composite coatings due to its excellent barrier effect and good compatibility with the coating matrix. In the aromatic ring of GO, the pore size of the regular hexagonal structure is only 0.064nm, which is much smaller than that of Cl − The van der Waals radius of corrosive media such as Mg (0.181nm), H2O (0.4nm) and O2 (0.346nm) can effectively block the diffusion of corrosive media.
[0004] However, due to the disadvantage that GO sheets are easy to agglomerate in the coating matrix, GO cannot be evenly dispersed and fully exert its excellent barrier properties. Therefore, it is necessary to develop a simple and effective method to achieve the controllable preparation of GO and the effective combination of graphene oxide and the coating matrix to improve the anti-corrosion performance of the coating. Summary of the invention
[0005] In view of the above problems existing in the prior art, the present invention provides a water-based anti-corrosion coating of graphene oxide and a preparation method thereof, which realizes uniform dispersion of graphene oxide in the coating system and forms an effective combination with the substrate, thereby effectively improving the anti-corrosion performance of the water-based coating.
[0006] The specific content of the invention is as follows: In a first aspect, the present invention provides a method for preparing a graphene oxide water-based anti-corrosion coating, comprising: The expanded graphite stack is used as an anode and the metal conductive material is used as a cathode, which are inserted into an electrolyte for electrochemical stripping. The electrolyte after the reaction is filtered, washed and centrifuged, and the supernatant is taken to obtain a graphene oxide dispersion. The graphene oxide dispersion liquid and the aqueous resin emulsion are fully mixed in a mass ratio of (0.8 to 1.6):1, and then fully mixed with a curing agent to obtain the graphene oxide water-based anti-corrosion coating; Wherein, the electrolyte is composed of a mixed system of a modifier and an inorganic acid / salt, and the molar ratio of the modifier to the inorganic acid / salt is: (0 ~ 0.5): (0.1 ~ 1); The mass ratio of the curing agent to the aqueous resin emulsion is (0.2 ~ 1.0): 1; The modifier is an amino modifier.
[0007] Optionally, in the graphene oxide dispersion, the concentration of the graphene oxide is 0.5 to 3 mg / mL.
[0008] Optionally, the amino modifier is selected from: one or more combinations of 2-aminobenzamide, 3,5-diaminobenzoic acid, polyaniline, 3,5-diaminobenzenesulfonic acid and polyvinylpyrrolidone.
[0009] Optionally, the inorganic acid is selected from one or more combinations of sulfuric acid, hydrochloric acid and phosphoric acid; and / or The inorganic salt is selected from one or more combinations of ammonium sulfate, sodium sulfate, potassium sulfate and sodium chloride.
[0010] Optionally, the expanded graphite stack is obtained by the following method: In an ice bath, the graphite raw material is uniformly mixed with concentrated sulfuric acid and hydrogen peroxide, and after standing at room temperature for 4 to 8 hours, a highly cross-linked expanded graphite stack is obtained.
[0011] Optionally, the graphite raw material is selected from one or more combinations of natural flake graphite, microcrystalline graphite, artificial graphite, and Kish graphite.
[0012] Optionally, the water-based resin emulsion is selected from one or more combinations of water-based epoxy resins, water-based acrylates and water-based polyurethanes.
[0013] Optionally, the curing agent is selected from one or more combinations of diethylenetriamine, triethylenetetramine, tetraethylenepentamine and polyamide.
[0014] Optionally, the graphene oxide water-based anti-corrosion coating is sprayed onto the surface of the metal substrate, cured at room temperature for 2 to 3 hours, and then transferred to a 40 to 80° C. oven for drying for 6 to 48 hours to form a 20 to 50 μm thick anti-corrosion protective coating; In the anti-corrosion protective coating, the mass proportion of the graphene oxide is 0.05-0.5 wt.%.
[0015] In a second aspect, the present invention provides a water-based anti-corrosion coating of graphene oxide obtained by the preparation method described in the first aspect.
[0016] Compared with the prior art, the present invention has the following advantages: The invention provides a method for preparing a graphene oxide water-based anticorrosion coating, comprising: using an expanded graphite deposit as an anode and a metal conductive material as a cathode, inserting them into an electrolyte containing a modifier, performing electrochemical stripping, filtering, washing and centrifuging the electrolyte after the reaction, taking a supernatant to obtain a graphene oxide dispersion; fully mixing the graphene oxide dispersion with a mass ratio of (0.8-1.6):1 and an aqueous resin emulsion, and then fully mixing with a curing agent to obtain the graphene oxide water-based anticorrosion coating; wherein the electrolyte is composed of a mixed system of a modifier and an inorganic acid / salt, and the molar ratio of the modifier to the inorganic acid / salt is: (0-0.5):(0.1-1); the mass ratio of the curing agent to the aqueous resin emulsion is (0.2-1.0):1, and the modifier is an amino modifier.
[0017] In the preparation method provided by the present invention, by constructing an electrolytic cell, deep oxidation and modification of the expanded graphite deposit are achieved in one step by means of electrochemical treatment. Since the graphene oxide itself has a certain hydrophilicity, after amino modification, its hydrophilicity is further enhanced, and its dispersibility in water or polar solvents is significantly improved. This allows the amino-modified graphene oxide to be more evenly dispersed in the application field of coatings, and good dispersibility can make the graphene oxide better combined with the matrix material, thereby improving the overall performance of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0019] Figure 1 A flow chart of a method for preparing a graphene oxide water-based anti-corrosion coating provided by an embodiment of the present invention is shown; Figure 2 The Raman scan image of the graphene oxide water-based anti-corrosion coating provided by the embodiment of the present invention is shown; Figure 3 A scanning electron microscope image of a cross section of a graphene oxide water-based anti-corrosion coating provided by an embodiment of the present invention is shown; Figure 4 A cross-sectional scanning electron microscope image of another graphene oxide water-based anti-corrosion coating provided by an embodiment of the present invention is shown; Figure 5 A cross-sectional scanning electron microscope image of another graphene oxide water-based anti-corrosion coating provided by an embodiment of the present invention is shown; Figure 6A scanning electron microscope image of a cross section of an anti-corrosion coating provided in a comparative example of the present invention is shown. DETAILED DESCRIPTION
[0020] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means a limitation on the present invention and its application or use. Based on the embodiments of the present invention, any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts falls within the scope of protection of the present invention. In addition, all other embodiments obtained by ordinary technicians in this field without carrying out creative work belong to the scope of protection of the present invention.
[0021] In the embodiment, no specific experimental steps or conditions are indicated, and the operation or conditions of the conventional experimental steps described in the prior art in this field can be carried out. The reagents used and other instruments that do not indicate the manufacturer are conventional reagent products that can be obtained commercially. In addition, the accompanying drawings are only schematic diagrams of the embodiments of the present invention and are not necessarily drawn to scale. The same reference numerals in the figures represent the same or similar parts, and thus their repeated description will be omitted. Some block diagrams shown in the accompanying drawings are functional entities and do not necessarily correspond to physically or logically independent entities.
[0022] Technologies, methods, and apparatus known to ordinary technicians in the relevant field may not be discussed in detail, but where appropriate, such technologies, methods, and apparatus should be considered part of the authorization specification.
[0023] In the description of the present invention, it should be understood that the use of terms such as "first" and "second" to limit components is only for the convenience of distinguishing the corresponding components. Unless otherwise stated, the above terms have no special meaning and therefore cannot be understood as limiting the scope of protection of the present invention.
[0024] In addition, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0025] The specific implementation contents of the present invention are as follows: In a first aspect, the present invention provides a method for preparing a water-based anti-corrosion coating of graphene oxide. Figure 1 The flowchart of the preparation method of the graphene oxide water-based anti-corrosion coating provided by the embodiment of the present invention is shown as follows: Figure 1 As shown, the following steps are included: S1. Using the expanded graphite deposit as an anode and the metal conductive material as a cathode, inserting them into an electrolyte containing a modifier for electrochemical stripping. The electrolyte after the reaction is filtered, washed and centrifuged, and the supernatant is taken to obtain a graphene oxide dispersion; When this step is specifically implemented, the graphite material involved in the electrochemical stripping is an expanded graphite stack, which is specifically a graphite raw material treated with concentrated sulfuric acid and hydrogen peroxide. After being treated with concentrated sulfuric acid and hydrogen peroxide, the graphite raw material is converted into graphene oxide, which has a rich structure with oxygen-containing functional groups such as carboxyl, hydroxyl, and epoxy groups, and the interlayer spacing is also increased compared to the original graphite. These changes have laid an important foundation for the subsequent electrolysis process. For example, the increased interlayer spacing makes it easier for the electrolyte to enter the interior of the material, so as to better participate in the electrolysis reaction; and the presence of oxygen-containing functional groups changes the electrical properties of the material, so that it has a different reactivity and behavior from the original graphite during electrolysis. In addition, due to the hydrophilicity brought by the surface functional groups, graphene oxide can have a better dispersion effect in water or suitable electrolyte solutions. Compared with the difficult dispersion of original graphite, this allows it to be more evenly distributed in the electrolyte during electrolysis, ensuring that the entire electrolysis process can be carried out more evenly in various parts, avoiding abnormal local reactions due to problems such as agglomeration, and is more conducive to achieving stable and predictable electrolysis reactions, helping to improve the uniformity of the product.
[0026] In some embodiments, the graphite raw material can be selected from one or more combinations of natural flake graphite, microcrystalline graphite, artificial graphite, and Kish graphite, preferably natural flake graphite.
[0027] When this step is specifically implemented, the highly cross-linked expanded graphite deposit is first transferred to a container with small holes evenly opened on all sides, and the material of the container is preferably plastic material, and then a conductive metal is inserted into the graphite deposit to complete the assembly of the anode; the metal material used as the cathode can be selected from platinum wire or platinum sheet, and the electrode thus constructed ensures that the expanded graphite deposit located at the anode only exists in the anode area of the electrochemical reaction, so that the graphite deposit can fully participate in the electrochemical intercalation and stripping reaction; at the same time, the stripped graphene oxide can be separated from the reaction area from the side wall through hole of the container, ensuring the normal progress of the subsequent electrochemical stripping and improving the yield of graphene oxide.
[0028] In some embodiments, the electrolyte is composed of a mixed system of a modifier and an inorganic acid / salt, and the molar ratio of the modifier to the inorganic acid / salt is: (0 ~ 0.5): (0.1 ~ 1); the amino modifier is selected from: one or more combinations of 2-aminobenzamide, 3,5-diaminobenzoic acid, polyaniline, 3,5-diaminobenzenesulfonic acid and polyvinylpyrrolidone. The presence of the amino modifier in the electrolyte allows the graphite deposit to be further electrolytically oxidized to graphene oxide. The introduction of amino groups increases the chemical affinity of graphene oxide with other materials, thereby improving the processing performance of amino-modified graphene oxide; for example, when preparing anti-corrosion coatings, amino-modified graphene oxide is easier to mix evenly with other matrix materials, and can better maintain its dispersed state during the processing, which is beneficial to improving processing efficiency and product quality. In addition, amino-modified graphene oxide can also interact with the active groups on the molecular chains of high-molecular polymers in the coating to form hydrogen bonds, covalent bonds, etc., thereby enhancing the interfacial bonding force between graphene oxide and the polymer; this enhanced interfacial bonding force helps to improve the overall mechanical properties of the coating, such as tensile strength, impact strength, etc., and enhance its durability.
[0029] S2. After fully mixing the modified graphene dispersion with a mass ratio of (0.8 to 1.6):1 with the aqueous resin emulsion, and then fully mixing with the curing agent, the graphene oxide water-based anti-corrosion coating is obtained.
[0030] When this step is implemented, the modified graphene dispersion obtained in the above step S1 has good dispersibility and chemical affinity with other materials. As a component of the anti-corrosion coating, it is fully mixed with the water-based resin emulsion according to a mass ratio of (0.8 ~1.6):1, and the resulting mixture is fully mixed with a certain amount of curing agent to obtain a graphene oxide water-based anti-corrosion coating. The concentration of the mixed graphene oxide dispersion is 0.5 ~ 3mg / m. The water-based resin emulsion is selected from one or more combinations of water-based epoxy resin, water-based acrylate and water-based polyurethane, and the curing agent is selected from one or more combinations of diethylenetriamine, triethylenetetramine, tetraethylenepentamine and polyamide.
[0031] Furthermore, the graphene oxide water-based anti-corrosion coating is sprayed onto the surface of the metal substrate, cured at room temperature for 2 to 3 hours, and then transferred to a 40 to 80 ° C oven for drying for 6 to 48 hours to form a 20 to 50 micron thick anti-corrosion protective coating. In the anti-corrosion protective coating, the mass proportion of graphene oxide is 0.05 to 0.5 wt.%.
[0032] In a second aspect, the present invention provides a water-based anti-corrosion coating of graphene oxide obtained by the preparation method described in the first aspect.
[0033] In order to enable those skilled in the art to understand the present invention more clearly, the graphene oxide water-based anti-corrosion coating and the preparation method thereof described in the present invention are now described in detail through the following examples.
[0034] Example 1 0.5 g of natural flake graphite (100 mesh) was uniformly mixed with 7 mL of concentrated sulfuric acid and 3.6 mL of hydrogen peroxide in an ice bath and allowed to stand at room temperature for 4 h to obtain cross-linked worm-like expanded graphite; the expanded graphite was transferred to a container with evenly distributed small holes on the wall as an electrochemical anode, a platinum wire as a cathode, and an electrolyte of 0.5 mol / L ammonium sulfate solution for electrochemical stripping; the reaction product was filtered, washed, and centrifuged to obtain a 1 mg / mL graphene oxide dispersion; 8 g of graphene oxide dispersion was weighed and mixed with 10 g of waterborne epoxy resin emulsion, and after stirring for 30 min, 5 g of curing agent diethylenetriamine was added and stirring was continued for 30 min to obtain a graphene oxide composite coating (graphene oxide content was 0.1 wt.%); The composite coating prepared above was sprayed onto the polished Q235 steel surface, cured at room temperature for 2 h until the surface was dry, and then placed in a 40 °C oven for drying for 48 h to obtain an anti-corrosion coating with a thickness of 42 μm.
[0035] Figure 2 The Raman scan of the graphene oxide water-based anti-corrosion coating provided by the embodiment of the present invention is shown. Figure 2 As shown, graphene oxide (GO) at 1350 cm −1 The D band of epoxy resin is 1100 cm −1 The normalized distribution of peak intensity ratios shows that electrochemically exfoliated graphene oxide can be uniformly dispersed in the water-based epoxy coating.
[0036] Figure 3 The cross-sectional scanning electron microscope image of the graphene oxide water-based anti-corrosion coating provided by the embodiment of the present invention is shown as follows: Figure 3 As shown, the addition of 0.1 wt.% graphene oxide reduces the voids and cracks generated during the coating curing process and improves the physical barrier properties of the coating.
[0037] Example 2 Under ice bath conditions, 0.5 g of natural flake graphite (100 mesh) was uniformly mixed with 7 mL of concentrated sulfuric acid and 3.6 mL of hydrogen peroxide, and allowed to stand at room temperature for 4 h to obtain cross-linked worm-like expanded graphite; the expanded graphite was transferred to a container with evenly distributed small holes on the wall as an electrochemical anode, a platinum wire as a cathode, and an electrolyte of 0.5 mol / L ammonium sulfate solution for electrochemical stripping; the reaction product was filtered, washed, and centrifuged to obtain a 1.5 mg / mL graphene oxide dispersion; Weigh 10 g of the graphene oxide dispersion and 10 g of the waterborne epoxy resin emulsion, stir for 30 min, then add 5 g of curing agent diethylenetriamine, and continue stirring for 30 min to obtain a graphene oxide composite coating (graphene oxide content is 0.2 wt.%); The composite coating prepared above was sprayed onto the polished Q235 steel surface, cured at room temperature for 2 h until the surface was dry, and then placed in a 40 °C oven for drying for 48 h to obtain an anti-corrosion coating with a thickness of 44 μm.
[0038] (The process of this embodiment is the same as that of embodiment 1. The difference is that 10 g of graphene oxide dispersion with a concentration of 1.5 mg / mL is weighed and mixed with the aqueous epoxy resin emulsion, and the thickness of the coating after curing is 44 microns).
[0039] Example 3 Under ice bath conditions, 0.5 g of natural flake graphite (100 mesh) was uniformly mixed with 7 mL of concentrated sulfuric acid and 3.6 mL of hydrogen peroxide, and allowed to stand at room temperature for 4 h to obtain cross-linked worm-like expanded graphite; the expanded graphite was transferred to a container with small holes in the wall as an electrochemical anode, a platinum wire as a cathode, and an electrolyte of a mixed system of 0.5 mol / L ammonium sulfate solution and 0.1 mol / L 2-aminobenzamide for electrochemical exfoliation; the reaction product was filtered, washed, and centrifuged to obtain a 1.2 mg / mL graphene oxide dispersion; Weigh 10 g of graphene oxide dispersion and 10 g of waterborne epoxy resin emulsion, mix them, stir for 60 min, add 3 g of curing agent tetraethylenepentamine, and continue stirring for 60 min to obtain graphene oxide coating (graphene oxide content is 0.15 wt.%); The composite coating prepared above was sprayed onto the polished Q235 steel surface, cured at room temperature for 2 h until the surface was dry, and then placed in an oven at 80 °C for 12 h to obtain an anti-corrosion coating with a thickness of 37 μm.
[0040] Figure 4 A cross-sectional scanning electron microscope image of another graphene oxide water-based anti-corrosion coating provided by an embodiment of the present invention is shown, as Figure 4 As shown in the figure, the addition of 0.15 wt.% graphene oxide makes the coating matrix denser, effectively fills the gaps and defects of the coating matrix, and is beneficial to the improvement of the corrosion resistance of the coating.
[0041] Example 4 Under ice bath conditions, 0.5 g of natural flake graphite (100 mesh) was uniformly mixed with 7 mL of concentrated sulfuric acid and 3.6 mL of hydrogen peroxide, and allowed to stand at room temperature for 4 h to obtain cross-linked worm-like expanded graphite; the expanded graphite was transferred to a container with small holes in the wall as an electrochemical anode, platinum wire as a cathode, and the electrolyte was a mixed system of 0.5 mol / L ammonium sulfate solution and 0.1 mol / L 3,5-diaminobenzoic acid for electrochemical exfoliation; the reaction product was filtered, washed and centrifuged to obtain a 0.5 mg / mL graphene oxide dispersion; 10 g of graphene oxide dispersion was weighed and mixed with 10 g of waterborne epoxy resin emulsion, and after stirring for 60 min, 2 g of curing agent polyamide was added, and stirring was continued for 60 min to obtain a graphene oxide composite coating; The composite coating prepared above was sprayed onto the polished Q235 steel surface, cured at room temperature for 2 h until the surface was dry, and then placed in an 80 °C oven for 12 h to obtain an anti-corrosion coating with a thickness of 41 μm (graphene oxide content of 0.05 wt.%).
[0042] (This embodiment is the same as the process of embodiment 3. The difference is that the electrolyte used is a mixed system of 0.5 mol / L ammonium sulfate and 0.1 mol / L 3,5-diaminobenzoic acid; the concentration of the prepared modified graphene dispersion is 0.5 mg / mL, and the thickness of the composite coating is 41 microns).
[0043] Example 5 Under ice bath conditions, 0.5 g of natural flake graphite (100 mesh) was uniformly mixed with 7 mL of concentrated sulfuric acid and 3.6 mL of hydrogen peroxide, and allowed to stand at room temperature for 4 h to obtain cross-linked worm-like expanded graphite; the expanded graphite was transferred to a container with small holes in the wall as an electrochemical anode, platinum wire as a cathode, and the electrolyte was a mixed system of 0.5 mol / L ammonium sulfate solution and 0.1 mol / L 3,5-diaminobenzoic acid for electrochemical exfoliation; the reaction product was filtered, washed and centrifuged to obtain a 3 mg / mL graphene oxide dispersion; Weigh 10 g of the graphene oxide dispersion, mix it with 10 g of waterborne epoxy resin emulsion, stir for 60 min, add 5 g of curing agent diethylenetriamine, and continue stirring for 60 min to obtain a modified graphene composite coating (graphene oxide content is 0.3 wt.% wt.%); The composite coating prepared above was sprayed onto the polished Q235 steel surface, cured at room temperature for 2 h until the surface was dry, and then placed in an oven at 80 °C for 12 h to obtain an anti-corrosion coating with a thickness of 38 μm.
[0044] (This embodiment has the same process as that of embodiment 4. The difference is that the concentration of the prepared modified graphene dispersion is 3 mg / mL, and the thickness of the composite coating is 38 microns.) Figure 5 A cross-sectional scanning electron microscope image of another graphene oxide water-based anti-corrosion coating provided by an embodiment of the present invention is shown, as Figure 5 As shown, the modified graphene with an addition amount of 0.3 wt.% still has good dispersion in the coating matrix, almost no defects and gains, and exhibits excellent corrosion resistance.
[0045] Example 6 Under ice bath conditions, 0.5 g of natural flake graphite (100 mesh) was uniformly mixed with 7 mL of concentrated sulfuric acid and 3.6 mL of hydrogen peroxide, and allowed to stand at room temperature for 4 h to obtain cross-linked worm-like expanded graphite; the expanded graphite was transferred to a container with small holes in the wall as an electrochemical anode, platinum wire as a cathode, and the electrolyte was a mixed system of 0.5 mol / L ammonium sulfate solution and 0.1 mol / L 3,5-diaminobenzoic acid for electrochemical exfoliation; the reaction product was filtered, washed and centrifuged to obtain a 3 mg / mL graphene oxide dispersion; Weigh 14 g of the graphene oxide dispersion and 10 g of the waterborne epoxy resin emulsion, mix them, stir for 60 min, add 5 g of curing agent diethylenetriamine, and continue stirring for 60 min to obtain a graphene oxide anticorrosive coating (graphene oxide content is 0.6 wt.% wt.%); The composite coating prepared above was sprayed onto the polished Q235 steel surface, cured at room temperature for 2 hours until the surface was dry, and then placed in an oven at 80° C. for drying for 12 hours to obtain a composite coating with a thickness of 42 μm.
[0046] (This embodiment has the same process as that of embodiment 3. The difference is that 14 g of 3 mg / mL graphene oxide dispersion is weighed and mixed with epoxy resin emulsion, and the thickness of the composite coating is 42 microns.) Comparative Example 1 In this embodiment, 10 g of water-based epoxy resin emulsion was mixed with 10 g of deionized water and 5 g of curing agent diethylenetriamine and stirred for 10 min to obtain a water-based coating without graphene oxide; the above coating was sprayed onto a pre-polished Q235 steel surface, cured at room temperature until the surface was dry, and then placed in a 60°C oven for 24 h to obtain a blank coating with a thickness of 40 μm.
[0047] Figure 6 The cross-sectional scanning electron microscope image of the anti-corrosion coating provided in the comparative example of the present invention is shown as follows: Figure 6As shown, the anti-corrosion coating shows obvious pores and defects, which are caused by the volatilization of solvents during the curing process of the epoxy resin matrix, providing a path for the penetration of corrosive media and resulting in poor anti-corrosion performance.
[0048] Experimental example At the same time, the anti-corrosion coatings prepared in the above Examples 1-6 and Comparative Example 1 were immersed in a 3.5 wt.% sodium chloride solution for 48 hours, and the corrosion rate of the metal substrate protected by the coating was calculated according to the Tafel electrochemical test. The test results are shown in Table 1: Table 1 Performance parameters of coating
[0049] It can be seen from the test data in Table 1 that the anti-corrosion coating provided by the embodiment of the present invention shows a lower corrosion rate than the blank coating of the comparative example, which indicates that the graphene oxide prepared by electrochemical stripping in the present invention can be evenly dispersed in the coating matrix, effectively filling the gaps formed inside the coating, extending the path of the corrosive medium through the coating, and improving the anti-corrosion performance of the coating.
[0050] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification.
[0051] For the method embodiments, for the sake of simplicity, they are all described as a series of action combinations, but those skilled in the art should know that the present invention is not limited by the order of the actions described, because according to the present invention, some steps can be performed in other orders or simultaneously. Secondly, those skilled in the art should also know that the embodiments described in the specification are all preferred embodiments, and the actions and components involved are not necessarily required by the present invention.
[0052] The above is a detailed introduction to a graphene oxide water-based anti-corrosion coating and a preparation method provided by the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea; at the same time, for a general technician in this field, according to the idea of the present invention, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A method for preparing a graphene oxide water-based anti-corrosion coating, characterized in that: include: The expanded graphite stack is used as an anode and the metal conductive material is used as a cathode, which are inserted into an electrolyte for electrochemical stripping. The electrolyte after the reaction is filtered, washed and centrifuged, and the supernatant is taken to obtain a graphene oxide dispersion. The graphene oxide dispersion liquid and the aqueous resin emulsion are fully mixed in a mass ratio of (0.8 to 1.6):1, and then fully mixed with a curing agent to obtain the graphene oxide water-based anti-corrosion coating; Wherein, the electrolyte is composed of a mixed system of a modifier and an inorganic acid / salt, and the molar ratio of the modifier to the inorganic acid / salt is: (0 ~ 0.5): (0.1 ~ 1); The mass ratio of the curing agent to the aqueous resin emulsion is (0.2 ~ 1.0): 1; The modifier is an amino modifier.
2. The method for preparing the graphene oxide water-based anticorrosive coating according to claim 1, characterized in that: In the graphene oxide dispersion, the concentration of the graphene oxide is 0.5 to 3 mg / mL.
3. The method for preparing the graphene oxide water-based anticorrosive coating according to claim 1, characterized in that: The amino modifier is selected from: one or more combinations of 2-aminobenzamide, 3,5-diaminobenzoic acid, polyaniline, 3,5-diaminobenzenesulfonic acid and polyvinyl pyrrolidone.
4. The method for preparing the graphene oxide water-based anticorrosive coating according to claim 1, characterized in that: The inorganic acid is selected from one or more combinations of sulfuric acid, hydrochloric acid and phosphoric acid; and / or The inorganic salt is selected from one or more combinations of ammonium sulfate, sodium sulfate, potassium sulfate and sodium chloride.
5. The method for preparing the graphene oxide water-based anticorrosive coating according to claim 1, characterized in that: The expanded graphite stack is obtained by the following method: In an ice bath, the graphite raw material is uniformly mixed with concentrated sulfuric acid and hydrogen peroxide, and after standing at room temperature for 4 to 8 hours, a highly cross-linked expanded graphite stack is obtained.
6. The method for preparing the graphene oxide water-based anticorrosive coating according to claim 5, characterized in that: The graphite raw material is selected from one or more combinations of natural flake graphite, microcrystalline graphite, artificial graphite and Kish graphite.
7. The method for preparing the graphene oxide water-based anticorrosive coating according to claim 1, characterized in that: The water-based resin emulsion is selected from one or more combinations of water-based epoxy resin, water-based acrylate and water-based polyurethane.
8. The method for preparing the graphene oxide water-based anticorrosive coating according to claim 1, characterized in that: The curing agent is selected from one or more combinations of diethylenetriamine, triethylenetetramine, tetraethylenepentamine and polyamide.
9. The method for preparing the graphene oxide water-based anticorrosive coating according to claim 1, characterized in that: The graphene oxide water-based anti-corrosion coating is sprayed onto the surface of the metal substrate, and after curing at room temperature for 2-3 hours, it is transferred to a 40-80° C. oven for drying for 6-48 hours to form an anti-corrosion protective coating with a thickness of 20-50 microns; In the anti-corrosion protective coating, the mass proportion of the graphene oxide is 0.05-0.5 wt.%.
10. A water-based anti-corrosion coating of graphene oxide obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Method for electrochemically preparing graphene oxide
CN113603084A
Kish graphite-based graphene oxide modified water-based paint, preparation method and composite coating of Kish graphite-based graphene oxide modified water-based paint
CN117050606A
Pre-treatment coating composition and a method for producing the same
US20190161354A1